The Integrated Thematic Learning with Immersed Type in Improving Students’ Motivation: Study at MI Tahsinul Akhlak Bahrul Ulum Surabaya - Syamsudin - Syamsudin; Luluk Safitri (Institut Agama Islam Negeri (IAIN) Tulungagung, 2020)
This research was conducted to know the implementation of an immersed type of integrated thematic learning model to improve student’s motivation at MI Tahsinul Akhlaq Bahrul Ulum, Surabaya. This research used descriptive qualitative method. Data collection in this research was participant observation category to the teachers and students at MI Tahsinul Akhlaq Bahrul Ulum, Surabaya. The technique of data analysis in this research was data reduction, data display, and drawing conclusion. The preparation processes was i) researcher examined everything that could improve student’s motivation, ii) researcher examined the basic competencies (KD) contained in the syllabus book, iii) researcher examined the teacher's book and student's book, iv) researcher examined the learning model that could improve student’s motivation, and v) researcher arranged Lesson Plan (RPP). The lesson plan was implemented in thematic learning at MI Tahsinul Akhlaq Bahrul Ulum, then analysis was conducted to relate the improvement of student’s motivation before and after thematic learning with Immersed type. The result showed that the integrated thematic learning with Immersed type could improve students’ motivation at MI Tahsinul Akhlaq Bahrul Ulum.